Mothers’ awareness towards child injuries and injury prevention at home: an intervention study - Carlsson, Anna (BMC Res Notes, 2016)
BACKGROUND: Most injuries to young children happen in the home. Therefore, this study aimed to investigate if extended individual information to mothers’ related to injury to children in the home and possible preventative actions has any effect on their awareness of the problem and if Sense of Coherence has an influence. METHODS: This was a quasi-experimental designed intervention study with a comparison group. Extended individual information with empowerment as the approach was used. RESULTS: Ninety-nine mothers of children under the age of 7 months participate. A questionnaire with sociodemographic data and questions regarding awareness towards prevention was used. Mothers who took part in the intervention significantly increased their awareness of the fact that child injuries take place at home when compared with the mothers in the comparison group, [OR 2.3, CI 1.3–4.3]. However, no significant improvement of awareness towards prevention was noted, neither any association to the mothers’ SOC-scores. CONCLUSION: This study showed that the intervention had a positive effect on mothers’ awareness towards the fact that child injuries are taking place at home, but it did not increase the mothers’ awareness towards prevention of child injury.